MODELING THE TEXT CONTENT BY MERGING COMMUNICATIVE FRAGMENTS - S. F. Lipnitsky (Informatika)
Mathematical model of the process of retelling the content of the test messages by the convergence of communicative fragments is proposed. Formally defined concepts such fragments, as well as the verbal-associative networks as models of domain knowledge and retell the texts. Algorithm description of the content of the text presented.